Principles And Tools for Endurance Training of Handball Players - Akimov Kurbaniyaz Jumaniyazovich; Akimov Jumaniyaz Erniyazovich (Zien Journals, 2024)
The main means of teaching handball, like other sports, is physical exercise, its role in solving tasks set at certain stages of training, tools for teaching movements, the quality of preparatory tasks, and improving physical movement skills and competencies are given.
Keywords: Handball; handball players; training steps; training tools